The Effect of Social Media Services on MSMEs Business Turnover Mediated by Customer Engagement Variables at Food and Beverage MSMEs in Balikpapan City - Turuallo, Nelly; Soesilowati, Etty; Soseco, Thomas (PT. EQUATOR SINAR AKADEMIA, 2025)
This study aims to examine the effect of social media services on business turnover of MSMEs in Balikpapan City, with the mediating variable of customer engagement. This study uses quantitative approach with cross-sectional design and path analysis method. The research population includes MSMEs in the food and beverage sector in Balikpapan, with a total sample of 258 MSMEs taken randomly. Data collection was conducted through a Likert scale-based questionnaire, and data analysis technique using path analysis. The results show that social media services have a significant influence on customer engagement and business turnover of MSMEs. In addition, customer engagement significantly mediates the effect of social media services on turnover. This means that the use of social media can increase customer engagement which leads to an increase in business turnover. The significance of value in the Sobel test shows that the mediating effect of customer engagement in this relationship is quite strong. The conclusion from this study is that customer engagement plays an important role in strengthening the impact of social media services on MSME business performance. Thus, MSMEs in Balikpapan are suggested to utilize social media more interactively in order to increase customer engagement, which in turn will lead to increased business turnover.